2017
DOI: 10.1002/joc.4992
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of cloud cluster over the steep southern slopes of the Himalayas observed by CloudSat

Abstract: ABSRACT A cloud cluster (CC) dataset is presented using CloudSat Cloud Profile Radar (CPR) observations from June to August, between 2006 and 2010. The CCs were defined by grouping contiguous cloud pixels using a defined criteria, including reflectivity, ‘cloud mask’, and topographic information. The characteristics of identified CCs were then analysed. Based on the complex topography of the southern Himalayas, four adjacent regions were selected, including the flat Gangetic Plains (FGP), the foothills of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Contoured frequency by altitude diagrams (CFADs) of radar echoes are a good indicator of the threedimensional structural characteristics of clouds or precipitation events (Chen, Fu, et al, 2017). Figure 4c shows the CFAD distribution of the Ku-band echo for this precipitation event.…”
Section: Morning Casementioning
confidence: 99%
“…Contoured frequency by altitude diagrams (CFADs) of radar echoes are a good indicator of the threedimensional structural characteristics of clouds or precipitation events (Chen, Fu, et al, 2017). Figure 4c shows the CFAD distribution of the Ku-band echo for this precipitation event.…”
Section: Morning Casementioning
confidence: 99%
“…In the process of gridding, R e was taken as the arithmetic mean of all the cloud pixels in the grid. In view of the physical meaning of τ itself, direct arithmetic averaging without considering the pattern of distribution within the grid produced a maximum error of 20 % (Chen et al, 2019). We therefore used the logarithmic mean to average τ to a 1 • grid.…”
Section: Resultsmentioning
confidence: 99%
“…Due to thermal and orographic forcing, the summertime QTP is dominated by convective cloud systems, which exist at a small horizontal scale, and are relatively shallow and very local (Kurosaki & Kimura, ; Gao et al, ; Fu et al, ; Luo et al, ; Rüthrich et al, ; Pan & Fu, ; Li & Zhang, ; Shang et al, ; Wang & Guo, ). Note that the warm and humid summer monsoon frequently reaches the steep southern slope of the QTP, making it conducive to the formation of unique cloud–precipitation distributions (Chen et al, ; Chen et al, ; Fu et al, ; Qie et al, ; Yan et al, ; Yan & Liu, ; Zhang et al, ). In particular, the southeastern QTP (SETP) exhibits high‐frequency convective cloud systems consisting of very high cloud cover and large‐areal precipitation (Kurosaki & Kimura, ; Li et al, ; Maussion et al, ; Tan et al, ; Tong et al, ; Yu & Fu, ), and is the source of many large rivers in Asia, including the Jinsha, Lancang, and Nujiang rivers (Tan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of observations from active and passive satellite instrumentation has enabled significant progress in the quantitative understanding of the horizontal and vertical spatial distribution of cloud systems over the southern QTP (Qie et al, ; Chen et al, ; Fu et al, ; Zhang et al, ; Chen et al, ; Yan & Liu, ; Luo et al, ; Li et al, ). For instance, Chen et al () revealed that the distribution of cloud top heights (CTH) gradually changes from bimodal (3 and 15 km) over the foothills of the Himalayas, to unimodal (7–9 km) over the QTP. There are two reflectivity peaks of cloud clusters over the steep slope of the southern Himalayas, corresponding to cirrus (stratus) and strong convection, whereas only a single peak occurs for cirrus (stratus) over the foothills of the Himalayas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation